Pengaruh Brand Image Terhadap Motivasi Berkunjung Tamu Di Sushi Tei Restaurant Pondok Indah Mall Jakarta - Suci Sandi Wachyuni; Wino Tandriano (Jurnal Sains Terapan Pariwisata, 2017)
Food and beverage are the primary survival needs for human being. Currently, restaurant business has increased drastically compare to the years before. Thus, there is much similar types of restaurants have opened. In order to differentiate their product, it is very important for restaurant to build a positive brand image. Positive brand image can motivate people to visit Sushi Tei Restaurant. The data is gathered through questionnaires, in order to answer the problem. The validity test and reability test then can be conducted after all the data is gathered. The Classical Assumption Test to determine the valuation of the regression is an unblased collinear estimator, which include Normality Test, Multicollinearity Test, Heteroskidastity Test, and Autocorrelation Test. Method of data analysis used are Pearson correlation, Coefficient Determination, Regression and Hypothesis testing. In this thesis, the writer used SPSS ver.20.0, 2015 to process data. Based on the calculation of SPSS ver.20.0, the data is valid, legitimate, and the reliability is in accordance with the provisions of Cronbach Alpha, Classical Assumption Test showed normal data, no Multicollinear, no Heterokidastity and no Autocorrelation. The analysis of correlation coefficients shows that the data obtained for 0,2745 is considered sufficient or moderate, and the coefficient of determination show 7,5% while of 92,5% is due to other factors. In regression testing if the brand image variable increases 0,330 will affect motivation visit variable 34,806. The result of hypothesis testing and T test show that value t is greater than t table (3,584 > 1,975) and the value of sig is 0,00 < 0,05 It can be conclude that Ho is refused and Ha is accepted, which means that there is significant relationship between brand image and the motivation visit Sushi Tei Restaurant.